A CONFESSIONAL DIVIDE? - Noll, Mark A. (Fides et historia, 2012)
The author reflects on the history of the Christian confessional divide in the U.S., including the Christian denominations of Protestant, Catholic and Orthodox. The author refers to two books relating to religion and higher education in the U.S., ''Contending with Modernity: Catholic Higher Education in the Twentieth Century'' by Philip Gleason and ''The Soul of the American University: From Protestant Establishment to Established Unbelief,'' by George Marsden. The author relates the topics of the books to the confessional communities of the various U.S. Christian denominations an the overall collective U.S. national history relating to Christianity.